Moroccan Arabic: The Battlefield of Language Ideologies - Marouane Zakhir; Jason L. O'Brien (JURNAL ARBITRER, 2019)
The debate on the use of Moroccan Arabic (also known as Moroccan darija) dates back to the medieval period when literary critics have discussed the effectiveness of writing in Moroccan Arabic lyrics of Muslim Spain, muwashshahat and zajal. This debate was later sharpened in the protectorate era (1912-1955) by the French colonial administration in its attempt to use MA in education as a tool to divide Morocco into Arabs and Amazigh, separate the country from the Arab world and pave the way for French to flourish in society. Nowadays, the use of MA in education came to the fore front of the interests of Moroccan intelligentsia. A new current of Francophone academics called for the legitimacy of using MA in education and media to fight illiteracy and maximize access to education in the country. They held many conferences for the sake of discussing the utility of MA as an alternative for SA in education and designed dictionaries and books to ease its instruction. Such attempts raised the hostility of Arabists and Amazigh activists. They regarded the defense of MA use in education as an ideology of language to eradicate Moroccan official languages in favor of French and the Francophone culture. The present empirical research examines the status of MA in education and the different ideologies backing its use by Moroccan teachers and students.